Degree resistance distance of unicyclic graphs - Ivan Gutman; Linhua Feng; Guihai Yu (Transactions on Combinatorics, 2012)
Let G be a connected graph with vertex set V(G). The degree resistance distance of G is defined as the sum over all pairs of vertices of the terms [d(u)+d(v)] R(u,v), where d(u) is the degree of vertex u, and R(u,v) denotes the resistance distance between u and v. In this paper, we characterize n-vertex unicyclic graphs having minimum and second minimum degree resistance distance.